Soft skill: Penting untuk Dikembangkan oleh Peserta Didik sebagai Bagian dari Kurikulum Merdeka - Hidayah, Nurul; Ningrum, Ayu Reza (STKIP PGRI Bandar Lampung, 2024)
The purpose of this research is to outline how students' soft skills develop during the planning, implementation, and evaluation stages of the independent curriculum. The study involved fourth-grade students, teachers, deputy principals for curriculum, and school principals, with a focus on enhancing students' soft skills through the independent curriculum. The research followed a qualitative descriptive approach and utilized data collection methods such as interviews, observation, and documentation. The collected data was analyzed through data reduction, presentation, and conclusion, with data validity ensured through source and technique triangulation. The results indicate successful implementation of the independent curriculum across its stages. Notably, at the planning stage, no soft skills development was observed. However, during implementation, various soft skills such as honesty, responsibility, justice, cooperation, adaptation, communication, tolerance, respect for others, decision-making, and problem-solving were observed. Moreover, at the evaluation stage, the developed soft skills included responsibility, cooperation, adaptation, tolerance, decision-making, and problem-solving.